Clinical Informatics in Psychiatric Training: Preparing Today’s Trainees for the Already Present Future - Torous, John; Chan, Steven; Luo, John; Boland, Robert; Hilty, Donald (Academic psychiatry, 2018)
The aptly titled article “Teaching to See Behaviors—Using Machine Learning?” published in August 2017 in Academic Psychiatry also notes that medical educators themselves must learn to teach new concepts that relate to the future of clinical psychiatry such as machine learning and reflects a growing awareness of the digital transformation occurring across all of healthcare [5]. [...]digital transformation is due to rapid advances in technology, which have expanded the role of clinical informatics in psychiatric service delivery, models of care, and clinical innovation. [...]government research institutes, such as the USA’s National Institute of Mental Health and whole health systems, such as the UK’s National Health Service, are actively promoting the use and development of such technologies. Residents are taught the principles of the Health Insurance Portability and Accountability Act (HIPAA) and secure data within the health system. Much interaction with mental health apps is done through Apple’s App Store and the Google Play Store, as opposed to an official formulary or evaluation process.